Savinova glasbena biografija in izvlečki iz njegove skladateljske korespondence - Ograjenšek, Suzana (Muzikološki zbornik, 2012)
Savin's surviving correspondence serves as a source for the composer's general biography as well as his music activities. At a rough estimate it comprises around 3000 documents; those devoted to music, including drafts, number over 550. This material, in connection to other new discoveries, offersa starting point for a new, updated music biography of Friderik Širca - Risto Savin. It helps chart four periods of Savin's composing creativity, which are defined differently from the periodization by Dragotin Cvetko.
Keywords: biografije; korespondenca; Osterc, Slavko; Pirnik, Makso; Savin, Risto; slovenska glasba; slovenski skladatelji; Zepič, Ludvik